The value of flexible vaccine manufacturing capacity: value drivers, estimation methods, and approaches to value recognition in health technology assessment - McElwee, F; Newall, A (Springer Nature, 2024)
Expanding flexible vaccine manufacturing capacity (FVMC) for routine vaccines could facilitate more timely access to novel vaccines during future pandemics. Vaccine manufacturing capacity is 'flexible' if it is built on a technology platform that allows rapid adaption to new infectious agents. The added value of routine vaccines produced using a flexible platform for pandemic preparedness is not currently recognised in conventional health technology assessment (HTA) methods. We start by examining the current state of play of incentives for FVMC and exploring the relation between flexible and spare capacity. We then establish the key factors for estimating FVMC and draw from established frameworks to identify relevant value drivers. The role of FVMC as a countermeasure against pandemic risks is deemed an additional value attribute that should be recognised. Next, we address the gap in the vaccine-valuation literature between the conceptual understanding of the value of additional FVMC and the availability of accurate and reliable tools for its estimation to facilitate integration into HTA. Three practical approaches for estimating the value of additional FVMC are discussed: stated and revealed preference studies, macroeconomic modelling, and benefit-cost analysis. Lastly, we review how value recognition of additional FVMC can be realised within the HTA process for routine vaccines manufactured on flexible platforms. We argue that, while the value of additional FVMC is uncertain and further research is needed to help to better estimate it, the value of increased pandemic preparedness is likely to be too large to be ignored.